Variation in nordic hamstring exercise force-angle relationship measures during a professional senior soccer season - Vazoukis, A.; Weaving, D.; Walker, J.; Emmonds, S. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Peak eccentric hamstring force is a popular measure during the Nordic hamstring exercise (NHE) to estimate injury risk [1]. However, peak force alone doesn`t fully reflect hamstring function during active lengthening. Hamstring injuries are associated with a shift in peak torque at a more flexed knee joint angle [2]. Therefore, examining the full force-angle relationship of the hamstrings can consider the interaction between knee joint angle and force production. This study aimed to construct the force-angle curve of hamstrings during the NHE and quantify the variability of the measures derived from this curve. METHODS: Twenty-three male soccer players participated from the same English Championship club (age: 27±5 y; stature: 1.83±0.06 m; body mass: 83.2±7.2 kg). A repeated-measures design was conducted during a competitive season whereby force- (NordBord [Vald Performance, Newstead, Australia]) and angle-time (video camera [Sony HXR-NX3/1 NXCAM]) data were collected during the NHE. Force- and angle-time data were synchronised and combined into force-angle profiles. Peak force (N), optimal angle (degrees; deg.), break-point angle (deg; BPA), and eccentric work done (J) were obtained from the force-angle curve of each limb. Players were assessed every 2-5 weeks across the season (8±2 [5 to 12] observations per player). They were instructed to perform the NHE at the slowest pace possible, while the video camera was capturing the movement in the sagittal plane. Data were analysed using mixed-effect models incorporating week as a fixed effect to account for any seasonal trend and player as random effect. Variance permitted to differ across players using a constant variance function structure, enabling estimation of individual standard deviations. Bootstrap resampling was then applied to calculate the overall coefficient of variation (CV; %) and corresponding 90% confidence intervals (CIs). RESULTS: The overall peak force, optimal angle, BPA, and eccentric work were 476.6±47.7 N, 114.3±6.4 deg,. 121.8±10.1 deg., and 13851±4127 J, respectively. The observed within-player variability expressed as CV (%, 90%CI) was 5.4% (4.4 to 6.4), 5.1% (4.4 to 5.7), 4.6% (4.0 to 5.2), and 17.7% (15.3 to 20.4) for these measures, in order. CONCLUSION: Peak force, optimal angle, BPA, and eccentric work presented very good (